2020
DOI: 10.1039/c9ra08459b
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of (−)-epigallocatechin-3-gallate inhibits T-cell acute lymphoblastic leukemia cell line HPB-ALL via the regulation of Notch1 expression

Abstract: T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy, and commonly associated with activating mutations in the Notch1 pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Recent studies have shown that EGCG has many excellent properties such as antitumor, antiradiation, and anti-oxidation capability [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, EGCG is sensitive to neutral and alkaline solutions and becomes unstable as the oxygen concentration, temperature, and pH increases, resulting in impossible direct usage in these environments [ 7 , 8 , 9 , 10 ]. In addition, EGCG is unstable in the gastrointestinal environment, leading to low bioavailability [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that EGCG has many excellent properties such as antitumor, antiradiation, and anti-oxidation capability [ 1 , 2 , 3 , 4 , 5 , 6 ]. However, EGCG is sensitive to neutral and alkaline solutions and becomes unstable as the oxygen concentration, temperature, and pH increases, resulting in impossible direct usage in these environments [ 7 , 8 , 9 , 10 ]. In addition, EGCG is unstable in the gastrointestinal environment, leading to low bioavailability [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…T8154; Sigma-Aldrich, St. Louis, Missouri, USA) staining was performed, and cell size determined using a JIMBIO FIL flow image counter (Jiangsu Zhuowei Biotechnology Co., Ltd., Changzhou, China). Chemical structure of D-EGCG.D-EGCG, dimeric (−)-epigallocatechin gallate [4].…”
Section: Analysis Of Cell Sizementioning
confidence: 99%
“…1. In previous research, D-EGCG has been found to exhibit anti-tumor activity [4], and the mechanism underlying the anti-tumor effects of D-EGCG warrants exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, Ag-catalyzed 6-endo-dig oxocyclization of β-alkynyl The Notch signaling pathway plays a diverse role during the development and maintenance of normal tissues, suggesting that the Notch pathway could be a novel cancer therapeutic target. [16] Recently, the tetrahydroquinolines have shown interesting properties against a variety of human cancer cell-lines, [17] especially in the Notch-dependent cell line, U937 [18] and HPB-ALL, [19] which means that the derivatives of tetrahydroquinoline have potential treatment effect of disease related to Notch. Hence, the anticancer activity of our newly synthesized compounds was evaluated in U937 cells.…”
mentioning
confidence: 99%